Ensino de ciências em uma perspectiva inclusiva : utilização de tecnologia assistiva com alunos com deficiência visual - Silva, Tatiane Santos (2014)
School inclusion of people with visual impairment should lead us to reflect how you are processing science teaching in inclusive schools. For the teaching of science and biology is characterized by extensive use of visual cues and are still scarce resources appropriate for teaching science aimed at students with visual impairment assistive technologies. Therefore, it is justified to consider a job using different assistive technology resources, tactile and sound, which can be used by these students , and the study of its feasibility of use. This study aimed to analyze the process of teaching and learning of Science with visually impaired students in a school of public schools in Aracaju, SE, as the use of assistive technology resources. Research uses qualitative approach adapting to molds case study. For data collection, the research was divided into three stages. At first, semi-structured interviews with students with visual impairments and their science teacher and not participating school interviews were conducted systematic observations. In the second step was performed in a validation group of different resources assistive technology developed by the researcher. In the third, the validated assistive technologies were used by teacher and students in science classes, that the opportunity was held not participating systematic observations. Finally, the opinions of survey participants was collected through semi - structured interviews after class. It can be noticed with this research, from the participants´ speech, that the conditions for learning science discipline, students with visual impairments included in this school are walking on the razor´s edge. Well, on one side there are the teachers interviewed, which have no initial or ongoing training about school inclusion of people with disabilities. Another, students with visual impairment, which merely "hear" the science classes, do assistive technology resources that provide access to strictly visual elements in science teaching were being used. According to students, the use of assistive technologies, which occurred in the third stage of this research, were extremely important to their learning because from these, they were able to access the knowledge of cells and tissues, since, according to them, without use of materials was difficult to understand the lesson. In short, we must go further and constantly hear actors inclusion, as students, subject teachers, specialist teachers of special education and all school staff, precisely because it is a recent, fluid and dynamic process that can be constantly improved as the reality that observes and experiences.